Examining perception of job satisfaction and intention to leave among ICU nurses in China - Hong Tao; Carol H. Ellenbecker; Yuefeng Wang; Ying Li (Elsevier, 2015)
Objectives: Previous studies in mainland China found ICU nurses to be less satisfied with their jobs and more inclined to leave them than are nurses in other hospital units. We aimed to determine ICU nurses' perspectives on the factors that influence job satisfaction and whether or not to continue working in the ICU. Methods: Nine ICU nurses were asked five open-ended questions to elicit the nurses' perspectives on job satisfaction and intentions to leave. Data were analyzed according to the process described by Knafl and Webster (1988). Core concepts were identified using the constant comparative method. Results: Two themes emerged as major influences on job dissatisfaction: 1) stress experienced from excessive workload demands and the ICU work environment, and 2) a lack of respect and recognition for the nurses' work. Two themes emerged as major influences on job satisfaction: 1) recognition of work, and 2) professional opportunities and relationships with coworkers. The effects of job satisfaction or dissatisfaction on the nurses' intentions to leave their jobs varied, although three categories were identified. Conclusions: For ICU nurses in China, sources of job dissatisfaction are potentially remedied with simple interventions. Adequate staffing is necessary but not sufficient for a positive work environment. Administrators should address the factors that directly affect their nurses' levels of job satisfaction, as it will ultimately result in less staff turnover and greater patient care.